2015
DOI: 10.5588/ijtld.14.0217
|View full text |Cite
|
Sign up to set email alerts
|

CD4 deficit and tuberculosis risk persist with delayed antiretroviral therapy: 5-year data from CIPRA HT-001

Abstract: Delays in ART initiation for HIV-infected adults with CD4 counts of 200-350 cells/mm(3) can result in long-term immune dysfunction and persistent increased risk for TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In addition, patients deemed too sick were also delayed. Apparently, patients considered too sick are at the greatest risk of developing TB [25]. Healthcare workers' education is therefore also needed to address this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients deemed too sick were also delayed. Apparently, patients considered too sick are at the greatest risk of developing TB [25]. Healthcare workers' education is therefore also needed to address this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Kanyerere, 1 B. Girma, 1,2 J. Mpunga, 1 K. Tayler-Smith, 3 A. D. Harries, 4,5 A. Jahn, 2,6 F. M. Chimbwandira 6 H uman immunodeficiency virus (HIV) infection is the most important risk factor for the development of tuberculosis (TB) in persons infected with Mycobacterium tuberculosis, and has been responsible for the huge upsurge in TB cases in affected southern African countries over the last 25 years. Antiretroviral therapy (ART) reverses the immune dysfunction associated with HIV, and with initiation of treatment there is rapid functional recovery of mycobacteria-specific immune responses, which results in enhanced capacity to restrict mycobacterial growth.…”
Section: Scale-up Of Art In Malawi Has Reduced Case Notification Ratementioning
confidence: 99%
“…3 More recent studies have confirmed these findings and have also highlighted the TB preventive benefits of early initiation of ART. [4][5][6][7] At the programme level, although PLHIV are often initiated late on ART and with low CD4 counts, studies from Malawi and Swaziland have shown that when high ART coverage rates are reached among HIV-infected populations, the TB case notification rate (CNR) decreases. [8][9][10][11][12] In a study from Malawi reporting data up to 2012, there was some preliminary evidence to suggest that while the declines in TB were most apparent in those with HIV infection, there might also be a decline in patients who were HIV-negative.…”
Section: Scale-up Of Art In Malawi Has Reduced Case Notification Ratementioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that person time accrued at lower CD4 strata is associated with an increased risk of tuberculosis after commencement of ART. 4,6 Implementation of integrated HIV and tuberculosis care programmes is essential to reduce the dual burden of disease.…”
Section: Introductionmentioning
confidence: 99%